Discrete, matched‐load, step‐up converter for 60–400 mV thermoelectric energy harvesting source. Issue 11 (1st May 2013) - Shuttleworth, R.; Simpson, K.
Abstract : A circuit is described that enables the output of a thermoelectric generator (TEG) to be boosted to around 5V over a TEG open circuit voltage range of 60 to 400mV. The topology has a JFET and MOSFET start‐up system which operates sequentially to charge a reservoir capacitor. When the capacitor is charged, the topology is converted to a discontinuous current mode flyback circuit which uses a BUZ11 MOSFET as the switch. The flyback circuit matches the converter input resistance to the TEG output resistance, thereby obtaining maximum power from the TEG. The circuit uses easily obtainable discrete components.